KONTRIBUSI TEOLOGI PEMBEBASAN BAGI FEMINISME DI ASIA: SEBUAH KAJIAN KRITIS - Jewadut, Jean Loustar; Gara, Urbanus; Hironimus, Jimmy Yohanes (Lembaga Penelitian STKIP Widya Yuwana, 2024)
Experiences of oppression, marginalization, and subordination have become a number of particular contexts that gave birth to critical reflections in a number of theologies such as liberation theology and feminist theology. The liberation theology project that was systematically promoted in Latin America in the mid-20th century began with the spread of colonialism, the political-economic hegemony of both national and transnational businessmen, and the massive use of a militaristic approach to various criticisms and resistance of oppressed people. Likewise, Asian feminist theology originates from criticism and resistance to patriarchal domination in the structure of religious, political, economic, cultural, and social life. Of course, these two theologies operate in the same context, namely the experience of oppression and marginalization of a group of people. This article was written using qualitative research methods with a focus on literature studies in the form of books and scientific journal articles according to the themes reviewed. The result of this study shows that liberation theology has contributed to feminist theology and the feminist movement in Asia. By being inspired by the approaches, methods and social analysis developed by liberation theology, the feminist movement in Asia dared to launch a progressive critique of the patriarchal and feudalistic face of the Church. Not only criticizing, feminism in Asia has reached a common movement, namely the establishment of a communion to oppose oppressive structures in shared life.